NILAI TAMBAH DAN PENGUATAN EKONOMI KELOMPOK USAHA BAJO INDAH LAPULU KENDARI MELALUI SEGMENTASI PASAR PADA DESAIN KEMASAN TERASI INSTANT - Surni .; Murdjani Kamaluddin (Agriplus, 2014)
This article the program is the following up of extension service facilitated by provincial planning board in year 2008 and 2009. The idea for producing “terasi” instant was based on experience that the wet “terasi” sold in markets is susceptible to contamination  from various descases vectors e,g fly, rat, and other insects, and also emits unwanted and rejected smell. However, this commodity is potentially dominates local, regional, as well as national markets when presented  in a more, hygienic, free from unwanted smell, more hygienic and attracted packaging, so it can be easity transported  every where. In this research, various “terasi” powder marketing levels from producer till retailers will be studied, including value added at producer level and value added at the retailer level. The first  targets are value added at producer level.  Results of value added analysis (input, output, and price) shouw that income obtained is Rp 68.630 kg-1 of terasi flour, which is the value added kg-1 of raw material, return to labour Rp 30.000 kg-1 of raw material; and the profit for members of farmer-processor group Rp 38.630 kg-1 of raw material. The value of production   (Rp 202.184,- kg-1) has big difference with the price of  raw material  (Rp 50.000,- kg-1 of raw material), so that the abtained value added is allocated more to labour the terasi processing operations. While the profit is allocated for the working capital of the farmed-processor group. Keywords: value added; terasi instant